Addressing substance abuse among healthcare professionals in a tertiary healthcare facility in Nigeria: a case study of Nnamdi Azikiwe university teaching hospital - Anagwu, Chidindu Prince; Edeh, Gabriel Chidera; Ekwebene, Onyeka Chukwudalu; Igwe, Timothy Ugochukwu; Nwankwo, Charles Chinedu; Agbo, Theophilus Nwanyigor; Okonkwo, Benjamin Chukwunonso; Nwafor, Kenneth Okezie (International Journal of Research in Medical Sciences, 2024)
Background: The use of psychoactive substances is prevalent worldwide, including among healthcare workers whose well-being, productivity, and effectiveness in addressing substance addiction in patients and the wider community can be significantly impacted. However, the extent of substance misuse among healthcare professionals in Nigeria, with its substantial social and public health implications, remains poorly understood. This research focused on the prevalence, attitudes, substances used, and influencing factors regarding substance misuse among staff at Nnamdi Azikiwe university teaching hospital (NAUTH) in Nnewi. Methods: A descriptive cross-sectional study was conducted involving 194 healthcare workers, using a multi-stage sampling method. Data were collected via a semi-structured self-administered questionnaire and analyzed with SPSS version 20. Results were presented in tables, considering p values less than 0.05 as significant. Results: Of the 197 respondents, 63.5% were female and 36.5% male, spanning various professions including doctors, nurses, and other healthcare specialists. Notably, 66% of participants had used substances in their lifetime. Alcohol was the most commonly abused substance, with significant percentages of moderate and high-risk users. Socialization and peer pressure were identified as the predominant factors influencing substance use, with significant statistical associations found between substance use and variables such as profession, sex, and duration of practice. Conclusions: The study highlighted a considerable prevalence of alcohol use among healthcare workers, who generally held a moderate view towards substance misuse and identified socialization and peer pressure as key factors. These findings underscore the pressing need for targeted training and intervention strategies for substance addiction among healthcare workers in Nigeria.